Social Determinants and Health Disparities Pertaining to Diabetes in Appalachia - Samuel Borgemenke; Allyson S. Hughes (SAGE Publishing, 2023)
Context: Diabetes poses a significant threat to public health in the United States, with an estimated total prevalence of 37.3 million individuals in 2019, of which 28.7 million were diagnosed and 8.5 million remained undiagnosed. The high prevalence of diabetes imposes a considerable economic burden on the U.S. healthcare system. Appalachian Ohio is disproportionately impacted with southeastern Ohio exhibiting a diabetes prevalence that exceeds the national average by more than twofold and a critical shortage of healthcare providers. Objective: To quantify the associations between diabetes prevalence and incidence in Ohio counties, considering various factors that impact health and quality-of-life outcomes. Methods: The data used in this study were obtained from the United States Diabetes Surveillance System (USDSS) on the 88 counties in Ohio. Pearson correlation tests were employed to investigate the relationship between diabetes (prevalence and incidence) and social determinants of health. A t -test and multivariate analysis of variance (MANOVA) test were performed to analyze the disparities in diabetes and social determinants between Appalachian and non-Appalachian counties. Results: The results of this study demonstrate notable disparities in diabetes prevalence between Appalachian and non-Appalachian counties ( P  < .001, α = .05). Furthermore, the MANOVA test revealed significant differences between these 2 groups regarding social determinants of health ( P  < .05). Conclusion: These findings suggest that Appalachian counties may face a disproportionate impact from health-related factors and experience limited access to healthcare services. The data highlight the need for focused efforts to address the specific challenges faced by Appalachian counties. Improving access to healthcare services in the Appalachian region is paramount to ensure equitable healthcare and enhance the overall health outcomes of affected communities.